Timber production and processing - Scutt, Deirdie (Wellington : Double D Technical Production, 2004)
Consist of part A and part B. Part A covers topics of classification and structure, harvesting, structure of a tree trunk, saw milling, drying of hardwoods and use of hardwoods. Part B discussed characteristics of commercial softwoods, plantation management, milling, drying, grading and etc.
Keywords: Timber